Días abiertos de un grupo de vacas Holstein (1989)
A study was conducted during an four years at the savanna of Bogota, whit 2.520 m.a.s.l. and an average temperature of 13.1°C, to analize open days' components in a group of 72 Holstein cows, with one to seven calvings. The parameters studied were: Calving to first postcalving heat; first heat to first service; first service to conception; services per pregnancy (sp) and days open which was the sum of the first three parameters above. Analysis of data indicated that the cows showed their first post-calving heat 61 ± 47 days after parturition; first service took place at 99 days and conception a 197 days, after calving, requiring 2.5 services per pregnancy. There was a stistically significant (P <0.05) effect of the number of calvings of the interval between first service and conception, this being especially notorious in cows with five, six and seven calvings. This interval was the main cause of the prolonged days-open period, and the relatively low number of services per pregnancy, suggest the need forfurther study of the causes ofthis long period after service.